A comparative study of pharmacological, nonpharmacological, and combined methods of induction of labor - Unmesh, Puri Sudha; Murlidhar, Bharati Vinod; Vikram, Latpate Raosaheb (European Journal of Clinical and Experimental Medicine, 2025)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. Induction of labor (IOL), a common obstetric procedure, aims to induce labor. The study defined labor induction success as true uterine contractions and classified delivery outcomes as vaginal, instrumental, and cesarean. A higher Bishop score predicts a vaginal delivery. The objective was to compare cervical status, induction success, cesarean section rates, and normal delivery rates of pharmacological and non-pharmacological IOL methods. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. In this study, 296 pregnant women admitted to the labor room were divided into three groups: those who received pharmacological agents (25 μg/50 μg misoprostol or dinoprostone 5 g gel to start labor), those who were giv en non-pharmacological agents (Foley’s catheter and membrane stripping to start labor), and those who were given both non-pharmacological and pharmacological agents (Foley’s catheter and membrane stripping followed by oxytocin to start labor). <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. Although a 92.5% induction success rate, the use of non-pharmacological methods alone led to a rate of 49.06% cesar ean section rate. Combined with a pharmacological agent such as oxytocin, it achieved almost the same success rate (91.43%) as a pharmacological method of inducing labor (18.57%). This resulted in a lower rate of cesarean section than pharmacological and nonpharmacological methods (p=0.002). <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. Nonpharmacological IOL methods alone led to higher cesarean rates despite improved cervical status. Combining them with pharmacological agents such as oxytocin resulted in higher normal delivery rates and fewer cesarean sections, indicating a more effective approach for improving delivery outcomes.